Educational Management Strategies for Internalizing Islamic Education Values in Shaping Students’ Disciplinary Character - Solehah, Imbrotus; Manshur, Umar (Al-Qalam Institue, 2025)
This study explores the strategies of internalizing Islamic Education (PAI) values in shaping students’ disciplinary character. Using a qualitative case study approach, data were collected through structured interviews with the principal, student counseling teacher, and vice principal for student affairs, complemented by direct observations and documentation. The findings indicate that discipline is cultivated through three main strategies: (1) habituation of positive character practices such as congregational prayers, Qur’an recitation, and daily courtesy routines; (2) teacher and staff role modeling, where educators serve as living examples of punctuality, honesty, and responsibility; and (3) consistent enforcement of school regulations linked to Islamic values. In addition, counseling strategies were applied through preventive, curative, and educative approaches, supported by collaboration with parents to ensure continuity at home. The study concludes that discipline is most effectively developed when Islamic values are internalized not as external obligations but as intrinsic aspects of students’ faith and behavior. The implications extend to educational management, highlighting the need for systematic planning, implementation, and evaluation of character education programs. By integrating pedagogical practices with management strategies, schools can foster sustainable discipline that contributes to producing responsible, ethical, and faith-driven future generations.